A Case-Control Study of Prone Positioning in Awake and Nonintubated Hospitalized Coronavirus Disease 2019 Patients. (11th February 2021) - Nauka, Peter C.; Chekuri, Sweta; Aboodi, Michael; Hope, Aluko A.; Gong, Michelle N.; Chen, Jen-Ting
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: To determine the association between prone positioning in nonintubated patients with coronavirus disease 2019 and frequency of invasive mechanical ventilation or inhospital mortality. Design: A nested case-matched control analysis. Setting: Three hospital sites in Bronx, NY. Patients: Adult coronavirus disease 2019 patients admitted between March 1, 2020, and April 1, 2020. We excluded patients with do-not-intubate orders. Cases were defined by invasive mechanical ventilation or inhospital mortality. Each case was matched with two controls based on age, gender, admission date, and hospital length of stay greater than index time of matched case via risk-set sampling. The presence of nonintubated proning was identified from provider documentation. Intervention: Nonintubated proning documented prior to invasive mechanical ventilation or inhospital mortality for cases or prior to corresponding index time for matched controls. Measurements and Main Results: We included 600 patients, 41 (6.8%) underwent nonintubated proning. Cases had lower Spo2 /Fio 2 ratios prior to invasive mechanical ventilation or inhospital mortality compared with controls (case median, 97 [interquartile range, 90–290] vs control median, 404 [interquartile range, 296–452]). Although most providers (58.5%) documented immediate improvement in oxygenation status after initiating nonintubated proning, there was no difference in worst Spo2 /Fio 2 ratios before and after nonintubated proning in both case and control (case median Spo2 /Fio 2 ratio difference, 3 [interquartile range, –3 to 8] vs control median Spo2 /Fio 2 ratio difference, 0 [interquartile range, –3 to 50]). In the univariate analysis, patients who underwent nonintubated proning were 2.57 times more likely to require invasive mechanical ventilation or experience inhospital mortality (hazard ratio, 2.57; 95% CI, 1.17–5.64; p = 0.02). Following adjustment for patient level differences, we found no association between nonintubated proning and invasive mechanical ventilation or inhospital mortality (adjusted hazard ratio, 0.92; 95% CI, 0.34–2.45; p = 0.86). Conclusions: There was no significant association with reduced risk of invasive mechanical ventilation or inhospital mortality after adjusting for baseline severity of illness and oxygenation status.